Komparasi Model Pembelajaran Inquiri Dan Problem Based Learning Terhadap Kemampuan Berpikir Kritis Ditinjau Dari Minat Belajar Siswa Pada Materi Pola Bilangan - Fetty Anggriani; Muhamad Firdaus; Hartono Hartono (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
The purpose of this research is to find out the comparison of Inquiry and Problem Based Learning learning models on critical thinking skills in terms of students' learning interests. This research was conducted at SMP Negeri 5 Sandai. This research was a quantitative experiment with the type of quasi-experimental design (quasi-experimental) research. The design of this study followed the research paradigm flow of Randomized Only Control Group Design where the subjects taken were grouped into two groups, namely experiment I and experimental group II. In this study, the samples were VIII grade students consisting of VIII A and VIII B classes. Experimental class 1, VIII A consisted of 30 students and experimental class 2, VIII B consisted of 30 students. The data collection tools used in this study were response questionnaires and tests of critical thinking skills in the form of essay questions. The results of the analysis of variance of the two cell paths are not the same indicating that there are differences in critical thinking skills between students with high, medium and low interest in learning. Based on the post-anava test with the Scheffe method, the value of F_(.1-.2) = 0.7374; F_(.1-.3) = 6.7540; F_(.2-.3) = 1.4279; DK = {Fâ”‚F<3.168}. From the results of the calculation of the two-way analysis of variance with unequal cells, the value of F_ab=1.576<F_(0.05;2;54)=3.16 means that H_0AB is accepted so that there is no interaction between the learning model and learning interest on students' critical thinking skills.